Study of Work-Hardening Rate Transient of AISI 409 Stainless Steel Under Strain Path Changes - Frederick Louis Dias de Morais; Elaine Carballo Siqueira Corrêa; Wellington Lopes (Materials Research, 2024)
Metal forming processes present many changes in the strain path necessary to obtain the dimensions and shape of a metal part. The loading mode, the amount of prestrain, the initial state of a material and its respective substructural arrangements affect the mechanical properties of different products. Many phenomena, such as the Bauschinger Effect, occur during a metal forming operation when the materials are subject to a mix of mechanical efforts. These events can be associated with changes in the dislocation substructure and crystallographic orientations. Considering the effect of strain path changes on the responses of metallic parts, this work investigates the mechanical behaviour of AISI 409 steel submitted to a loading route composed of cold rolling, tensile and shearing operations, modifying the direction of the last loading. The results indicated the effect of tensile effort and the respective dislocation substructure on the occurrence of work-hardening rate transient for the shearing carried out at 0° and a minor effect for the shearing conducted at 45° due to non-significant changes on the dislocation substructure.